Theoretical evidence of high power conversion efficiency in double perovskite solar cell device - Kumar, Manish; Raj, Abhishek; Kumar, Arvind; Anshul, Avneesh (Optical materials, 2021)
Power conversion efficiency (PCE) of inorganic lead-free double perovskite La2NiMnO6 photovoltaic material has reached 15.42% with considerably enhanced parameters of the absorbing layer. Herein, to find overall optimization for the present solar cell device, a comprehensive study is performed using the SCAPS simulation and first principle density functional theory (DFT) calculations, which may be easily control in the experimental laboratory. The double perovskite La2NiMnO6 is used as an absorbing layer in the heterostructure with TiO2 as an electron transport layer (ETL) and CuI as a hole transport layer (HTL). The impact of thickness, defect density, doping concentration, electron affinity of the absorber, various back metal contacts, and hole transport materials are taken into account for the optimization of the device. Firstly, the device is optimized with its experimental counterpart and shows the high possible power conversion efficiency after the variation in its absorbing layer parameters. If this efficiency will be confirmed in the laboratory then this lead-free inorganic double perovskite material may offer pronounced potential as a substitute, highly efficient material for the photovoltaic applications as an absorbing layer. The final optimized device performance parameters are as following: PCE = 15.42%, FF = 55.57%, Jsc = 40.64 mA/cm2 and Voc = 0.6828 V. The quantum efficiency is also investigated with respect to the thickness of the absorber, ETL, and HTL layers of the device and observed an enhancement in the quantum efficiency with the increase in absorber layer thickness. [Display omitted] •PCE of inorganic lead-free double perovskite La2NiMnO6 photovoltaic material is reported ~15.42%.•SCAPS simulation and first principal DFT calculations are used for the theoretical analysis.•Optimization of device parameters with its experimental counterpart.•Enhancement in the %QE with the variation in the absorber layer.•Final performance: %PCE = 15.42%, %FF = 55.57%, Jsc = 40.64 mV/cm2 and Voc = 0.6828 V.